Spacing Effect on the Height-diameter Relationship of Irrigated Shelterbelt Plantations in Hot Desert - Tewari, V. P.; Kumar, V. S. Kishan (Indian Forester, 2003)
A study was conducted to observe the effect of spacing on the height and diameter relationships of tree species planted as shelterbelts in hot arid areas under irrigated conditions. Generally, spacing of 3m Ã— 3m was found to be suitable for getting good height for the trees at a given diameter. Among all the species and spacings studied, E. camaldulensis at 3m Ã— 3m spacing is found to be most appropriate for raising shelterbelts in the study area to diffuse the upper wind flows.